French-German Military Cooperation and European Defence : From Driving Engine to Divergence of Interests? - Deschaux-Dutard, Delphine (Routledge Studies in European Security and Strategy., 2025)
This book examines the role of French-German cooperation within European military cooperation and European defence, and particularly the CSDP (Common Security and Defence Policy). The work explores whether Franco-German bilateral leadership is still relevant in European defence and military cooperation at the EU level, and analyses the reasons for its difficulties in the current context of the return to conventional warfare on the European continent. With an innovative research design that mixes a conceptual framework (discursive institutionalism) with tools from the sociology of International Relations, the book offers both a macro- and an actor-level perspective. The focus on the strategic discourses of both French and German actors, and the institutional settings within which these discourses develop, also enables to better grasp the complexity of military cooperation and the recurring limits of bilateral leadership by Paris and Berlin. Based on extensive fieldwork in Paris, Berlin and Brussels over the past two decades, including data collected since 2022, the book offers a longitudinal view of the issue as well as the most recent developments since the outbreak of the war in Ukraine. This book will be of much interest to students of European security, European politics and security studies in general.